Prof. Ts. Dr. Mohd. Rosli Hainin appointed as UMP Deputy VC Academic International - UMP, PNC (2019)
The Ministry of Education has appointed Professor Ts. Dr. Mohd. Rosli Hainin as Universiti Malaysia Pahang (UMP) Deputy Vice-Chancellor (Academic & International) for three years effective from November 1, 2019 until October 31, 2022.